STUDY ON ENVIRONMENTAL FACTORS IN ELDERLY HOUSE : Life Science - Architecture - ISLAMI BAROUGH, BEHNAZ; HADAFI, FARZANEH (International Journal of Life Science and Pharma Research, 2017)
In recent years, fast increase in number of the elderly entails numerous consequences. Majority of the elderly are counterproductive people economically, isolated socially and subjected to the risk of chronic diseases, disability and disability caused by it in terms of health. As a result finding a solution and factors which are effective in increase of satisfaction and quality of life among the elderly and designing a favorable enviornment for the elderly are of great importance. In this regards, with study and analysis on enviornmental factors contributed in elderly’s life satisfaction, it was specified that however enviornmental factors are consistent with their signifying aspects such as sense of place and sense of space at physical environment, no favorable quality at the elderly house has achieved; one of the major reasons is architects’ lack of deep understanding of the elder’s human needs and lack of recognizing his needs, thus it seems that firstly the elderly’s mental, emotional and personality characteristics and their physical limitations have to be recognized so as to meet their needs and then suitable living environment including qualitative environmental issues(place and space) which their major characteristics have undergone negligence have to be made for them by considering the factors mentioned above. In the present research, factors affecting increase in environmental quality of elderly’s houses using questionnaire, interview, field observation have been recognized and classified and the required environmental factors in design of suitable house for their living have been recognized. The exploratory factor analysis has been the research method used in this article. The results from research indicate that residents’ satisfaction with elderly’s house environment (place and space) among the environmental factors has the highest effect in increase of elderly’s life satisfaction and quality.